2008
DOI: 10.1159/000127344
|View full text |Cite
|
Sign up to set email alerts
|

The Hemostatic Properties of Transurethral Plasmakinetic Resection of the Prostate: Comparison with Conventional Resectoscope in an ex vivo Study

Abstract: Aim: To compare the hemostatic properties of transurethral plasmakinetic resection of the prostate (PKRP) and standard transurethral resection of the prostate (TURP) ex vivo, as perioperative bleeding is still regarded as one of the major complications of transurethral prostatectomy. Materials and Methods: Isolated normal saline (NS)-perfused porcine kidneys were used to determine the hemostatic efficacy of PKRP and TURP. The perfusion fluid loss was semiquantitatively measured in relation to tissue ablation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Such complications can be a significant cause of morbidity in patients undergoing TURP, as they might mean the need for re‐operation or blood transfusion. The reasons for the observed haemostatic advantages of B‐TURP are not entirely clear, although some trials have suggested that bipolar energy results in deeper coagulative effects .…”
Section: Discussionmentioning
confidence: 99%
“…Such complications can be a significant cause of morbidity in patients undergoing TURP, as they might mean the need for re‐operation or blood transfusion. The reasons for the observed haemostatic advantages of B‐TURP are not entirely clear, although some trials have suggested that bipolar energy results in deeper coagulative effects .…”
Section: Discussionmentioning
confidence: 99%
“…As theoretical support, some ex vivo experiments have shown that a bipolar current has the nature of deep coagulation and a ''cut-and-seal'' property. [24][25][26] The authors indicated that these characteristics may contribute to a good hemostasis capacity of B-TURP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several ex vivo studies have confirmed the superior capability of bipolar current to achieve better haemostasis through deeper coagulation and through the so called ‘cut-and-seal’ effect of plasma produced by bipolar current [13], [14], [15].…”
Section: Discussionmentioning
confidence: 98%